The durability of the pulmonary autograft after Ross procedure in patients with rheumatic aortic valve disease - Ahmed Magdi Youssef; Waheed Etman; Akram Refaat Allam; Ahmed Mahgoub; Karimeldeen Hafez; Ahmed Afifi (Alexandria Journal of Medicine)
Background The pulmonary autograft is the ideal aortic valve substitute in young patients with aortic valve disease. Performing Ross procedure in patients with rheumatic heart disease is controversial as the autograft might be susceptible to recurrent rheumatic activity and early autograft dysfunction. The aim of the study is to evaluate the durability of the pulmonary autograft in series of patients with rheumatic aortic valve disease. This is a retrospective study enrolling patients who were admitted for Ross procedure and had a preoperative diagnosis of rheumatic heart disease from October 2009 to July 2021. Preoperative, intraoperative and postoperative data were collected from hospital records. Follow-up transthoracic echocardiogram was used to assess the autograft function, and Kaplan–Meier Curve was plotted to evaluate freedom from autograft dysfunction.Results The study included 28 patients who had Ross procedure with root replacement technique. The primary valve derangement is aortic regurgitation, and concomitant mitral disease requiring surgery was found in 32% of the patients. No operative mortality was recorded, and only one patient had late death throughout the follow-up period. Follow-up was complete in 75% of the cohort and the median follow-up was 4.75 years (range from 2 to 11.9 years). Freedom from any autograft dysfunction was 94.7% at 10 years. None of the patients required reintervention for the pulmonary autograft. Three patients had a total of 4 reinterventions; 2 for the homograft and 2 for the mitral valve.Conclusions Ross procedure remains a good option for replacing the aortic valve in young patients with rheumatic heart disease in the light of the good durability of the pulmonary autograft and the superior survival. Although longer follow-up duration and bigger sample size is needed to draw more significant results, the excellent initial outcomes guided by experienced hands should promote the use of Ross procedure in such cohort of patients.